Justice Social in the Age of Gig Economy: Reconstructing Legal Positivism to Draft Regulations Digital Jobs - Raden Ferdiandra Defry Yusdanial; I Wayan Mustika Eko Yuda (Journal Equity of Law and Governance, 2025)
The era of the gig economy has change landscape global employment, including in Indonesia, with emergence platform-based digital jobs such as online motorcycle taxis, workers freelance, and freelancer. Although offer flexibility, system This present challenge significant regulation, especially in protect rights digital workers. Existing regulations, which are dominated by law positivism, often focused on certainty law but fail to accommodate justice social for workers. As a result, many digital workers are in a legal status that is not clear, without social protection and basic rights. Research This aims for reconstruct law positivism to be able to compile regulation equitable digital jobs. With approach philosophical and normative, research This analyze weakness law positivism in context digital work, highlighting challenge main such as worker status (employee vs independent contractor), protection social, and relationships complex work in digital platforms. Based on analysis of literature law, international regulation, and studies case, research proposes a reconstruction model law that integrates principal social justice in framework law positivism. Research results show that law positivism need transform from approach formalistic to a more approach adaptive and inclusive. Reconstruction This includes: (1) recognition of legal status hybrid digital workers, (2) compilation mechanism protection universal social for worker gig economy, and (3) development system supervision based on technology for supervise digital platform compliance with regulation. Research novelty This lies in the development of regulatory models based on law Accommodating positivism justice social for digital workers in the gig economy era. This model offers practical and theoretical solutions. For create a system balanced regulation between certaifor law and protection rights workers, at the same time become runway for legal reform employment in the digital era.